Donor hypernatremia is associated with increased mortality after heart transplantation: A retrospective study. Issue 12 (20th September 2022) - Oehler, Daniel; Immohr, Moritz Benjamin; Böttger, Charlotte; Bruno, Raphael Romano; Sigetti, Dennis; Haschemi, Jafer; Aubin, Hug; Horn, Patrick; Tudorache, Igor; Westenfeld, Ralf; Akhyari, Payam; Kelm, Malte; et al.
Abstract: Background and aims: Donor hypernatremia has been associated with primary graft dysfunction in heart transplantation (HTx) and is correlated with impaired outcome following liver and renal transplantation. However, controversial data exist regarding the impact of sodium dysregulation on survival. This study aims to investigate the impact of donor sodium levels on early morbidity and short‐ and midterm survival following HTx. Methods: Between September 2010 and June 2021, a total of n  = 218 patients underwent HTx in our center. From those, 214 could be included retrospectively in our study. For each donor, sodium levels were collected and different cut‐off levels from 145 to 159 mmol/L were investigated by Kaplan‐Meier‐analysis. Then, recipients were divided in three groups regarding donor sodium: Normonatremia (133–145 mmol/L, n  = 73), mild hypernatremia (146–156 mmol/L, n  = 105) and severe hypernatremia (>156 mmol/L, n  = 35). Recipient and donor variables were reviewed and compared, including peri‐ and postoperative characteristics and recipient survival after up to 5 years after transplantation. Results: All patients were comparable regarding baseline characteristics and perioperative parameters. Regarding early mortality, 90‐day survival was significantly reduced only in patients with severe donor hypernatremia in comparison to normonatremia (90% vs. 71%, p  = .02), but not in mild hypernatremia (89%, p  = .89). One‐year survival was comparable in all groups ( p  > .28). Conclusion: Severe donor hypernatremia was associated with reduced short‐term survival, while the correlation weakens > 1 year after HTx. As our study is limited due to the nature of its retrospective, single‐center approach, future prospective studies are needed to evaluate the importance of donor management with regard to hypernatremia.